UJI KEKUATAN LASAN FRICTION STIR SPOT WELDING DIBAWAH PEMBEBANAN GESER TARIK PADA PADUAN ALUMINIUM - Randy Firmansyah (2022)
Technological advances in the emerging manufacturing sector are inseparable from welding as it plays an important role in metal fabrication and repair. Over the years improvements to increase productivity related to aluminum alloys in the manufacturing industry, has been widely researched and expanded. Problems in manufacturing today require fast and accurate processes to improve product quality in line with the spirit of the Industrial Revolution 4.0. In this study, aluminum sheet 1100 1 mm thick was welded using friction stir spot welding (FSSW) method and tested through tensile shear load test to determine the strength characteristics of the friction stir spot welding Weld results and also the influence on the combination of parameters such as spindle speed, tool depth, and residence time to the tensile shear load at the connection. The results showed that in each series of parameter combinations showed an attractive influence on tensile shear loads. The effect of 1400 rpm spindle speed showed good properties with the highest value of 71 MPa, especially at a tool depth of 0.6 mm. Furthermore, the influence of the tool depth has a significant effect on the tensile shear load, especially at 0.6 mm for each set of spindle speed and residence time. Each set of dwell time to the combination of parameters has no significant effect on the tensile shear load. Good tensile shear loads can be achieved in the range of 63-71 MPa at a tool depth of 0.6 mm and a spindle speed of 1400 rpm, where the best is 71 MPa at a standstill time of 9 seconds.